Reflections on the Petition Right Juridical Warranty in the Romanian Constitutional Law Doctrine - Cătălin-Radu Pavel (EIRP Proceedings, 2018)
The petition right, as a fundamental right of the Romanian citizen has the character of juridical warranty because this right is guaranteed by the Constitution and also is a substantive law. By granting the petition right is assuring a good administration of the state in the citizens’ favor. The aims and the objectives of the present research is to present the fundamental petition right of the Romanian citizen at the doctrine level and the characteristics of this guarantee right. Regarding the prior work, the analyses conducted so far have dealt less frequently with the topic approached here. The approach used in the present study was to analyze the Romanian constitutional doctrine. The results of the present study are important to the social society because it makes the correlation between the petition right and the good administration. The paper is original and it brings value from the perspective of the granting the right to petition at a constitutional level which ensures the protection of the citizens in relation with the public authorities and also to other rights, liberties and citizen interests, thus ensuring a good administration of the State to the benefit of its citizens.